1998
DOI: 10.1007/s001470050098
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diverticulosis and incidence of bowel perforation after kidney transplantation in patients with polycystic kidney disease

Abstract: Sigmoid perforation due to diverticulitis is a life-threatening complication in the postoperative course of allogenic kidney transplantation. The incidence of diverticulosis is especially high among patients with autosomal dominant polycystic kidney disease (ADPKD). Thus, those who undergo allogenic kidney transplantation represent a high-risk group. The aim of this study was to evaluate the prevalence of diverticulosis in ADPKD patients awaiting renal transplantation and the incidence of bowel perforation fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Nevertheless, the incidence rate of acute abdomen in the presented population (6%) was lower than in previous reports [3,5,6,15,18,[23][24][25], but the mortality rate in cases of abdominal emergency interventions performed (28%) is comparable. Comparable data are also reported for other organ transplant settings especially in kidney transplantation, with diverging results to mortality and morbidity [26][27][28].…”
Section: Discussionsupporting
confidence: 68%
“…Nevertheless, the incidence rate of acute abdomen in the presented population (6%) was lower than in previous reports [3,5,6,15,18,[23][24][25], but the mortality rate in cases of abdominal emergency interventions performed (28%) is comparable. Comparable data are also reported for other organ transplant settings especially in kidney transplantation, with diverging results to mortality and morbidity [26][27][28].…”
Section: Discussionsupporting
confidence: 68%
“…Of six case series involving a total of 186 patients with PKD [ 80 , 81 , 82 , 83 , 84 , 85 ], three made statements about the prevalence of diverticulosis. Scheff et al [ 80 ] documented a prevalence of 10/12 (83%), Dominguez Fernandez et al [ 82 ] of 15/28 (53.5%), and Sharp et al [ 83 ] of 28/59 (47%). In a group of patients with kidney failure but no PKD, Scheff et al [ 80 ] documented a diverticular prevalence of 10/31 (32%).…”
Section: Risk Factor Comorbiditymentioning
confidence: 99%
“…One risk factor for death was pre-existing kidney disease with an OR of 18.7 [ 86 ]. Of six case series including a total of 186 patients [ 80 , 81 , 82 , 83 , 84 , 85 ], four made statements about the incidence of diverticular disease. Scheff et al [ 80 ], Lederman et al [ 84 ], and Pourfarziani et al [ 85 ] reported high incidence of severe cases in particular, at 4/12 (33%), 12/59 (20%), and 3/18 (17%), respectively.…”
Section: Risk Factor Comorbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increased risk of colonic complications in renal transplant recipients, particularly in aged subjects and in patients with polycystic kidney disease [43]. Cecum or ascending colon hemorrhage can occur in association with severe CMV infection.…”
Section: Colon Disordersmentioning
confidence: 99%